2019
DOI: 10.1002/cbdv.201900056
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antimicrobial Activities, and Molecular Docking Studies of Dihydrotriazine Derivatives Bearing a Quinoline Moiety

Abstract: In this article, three series of dihydrotriazine derivatives bearing a quinoline moiety (5a, 5b, 8a–8c, and 9a–9m) have been designed, synthesized, and evaluated as antibacterial agents. Compounds 8a–8c were found to be the most potent of all of the compounds tested with an MIC value of 1 μg/mL against several Gram‐positive (S. aureus 4220 and MRSA CCARM 3506) and Gram‐negative (E. coli 1924) strains of bacteria. In addition, 3‐[4‐amino‐6‐(phenethylamino)‐2,5‐dihydro‐1,3,5‐triazin‐2‐yl)‐6‐[(3‐chlorobenzyl)oxy]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The theoretical conformation of the ligands with the highest biological activity is presented in Table 3 and Figure 3 with favorable contacts with the attachment site presented. The docked structures were examined by using Discovery Studio 4.5 Visualizer ( Jia et al, 2015 ; Rehman et al, 2018 ; Bai et al, 2019 ; Riaz et al, 2019 ) and Chimera 1.9 ( Withana-Gamage et al, 2011 ; Nietzel et al, 2013 ; Withana Gamage, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical conformation of the ligands with the highest biological activity is presented in Table 3 and Figure 3 with favorable contacts with the attachment site presented. The docked structures were examined by using Discovery Studio 4.5 Visualizer ( Jia et al, 2015 ; Rehman et al, 2018 ; Bai et al, 2019 ; Riaz et al, 2019 ) and Chimera 1.9 ( Withana-Gamage et al, 2011 ; Nietzel et al, 2013 ; Withana Gamage, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical conformation of the ligands with the highest biological activity is presented in Table 3 and Figure 3 with favorable contacts with the attachment site presented. The docked structures were examined by using Discovery Studio 4.5 Visualizer (Jia et al, 2015;Rehman et al, 2018;Bai et al, 2019;Riaz et al, 2019) and FIGURE 1 | (A) Protein motif analysis of antimicrobial signatures (shown in the same color) in napin genes using the PRINTS database. BNANAPINA = Q7DMU4_BRACM = Napin (Q7DMU4) from Brassica campestris; 2SS1_BRANA = Napin-1 (P01091), 2SSI_BRANA = Napin-1A (P24565), 2SSB_BRANA = Napin-B (P27740), 2SS2_BRANA = Napin-2 (P01090), 2SS3_BRANA = Napin-3 (P80208) and 2SSE_BRANA = Napin embryo-specific protein (P09893) are from Brassica napus, ALL1_SINAL = Allergen Sin a 1 (P09893) is from Sinapis alba, and 2SS2_CAPMA = Sweet protein mabinlin-2 (P30233) and 2SS4_CAPMA =Sweet protein mabinlin-4 (P80353) are from Capparis masaikai.…”
Section: In Silico Molecular Dockingmentioning
confidence: 99%
“…The compound 232 a was docked against DHFR that showed hydrogen bonding interaction with active site amino acid like Ile14 and Gln19 of DHFR. [62] Sanduja et al reported uracil clubbed coumarin derivatives (Scheme 46) and screened against six cancer cell lines such as Colo-205, A-549, MCF-7, PA-1, PC-3 and Hela cells using SRB assay. The compound 239 a was highly potent against MCF-7 cell line with GI 50 value of 1.55 μM.…”
Section: Chemistryselectmentioning
confidence: 99%
“…24 Xue-Qian Bai et al have reported synthesis, antimicrobial activities, and molecular docking studies of dihydrotriazine derivatives bearing a quinoline moiety. 25 Additionally, these drugs were characterized by their chemical structure: amino alcohols (quinine, mefloquine, lumefantrine, halofantrine), 4-aminoquinolines (chloroquine, amodiaquine, piperaquine, pyronaridine), 8-aminoquinoline (primaquine), naphthoquinone (atovaquone), antifolates (sulfadoxine-pyrimethamine, proguanil), endoperoxides (artemisinin and its derivatives) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%